TRAGIC NOISE AND RHETORICAL FRIGIDITY IN LYCOPHRON'S ALEXANDRA. (May 2021) - Nelson, Thomas J.; Molesworth, Katherine
Abstract: This paper seeks to shed fresh light on the aesthetic and stylistic affiliations of Lycophron's Alexandra, approaching the poem from two distinct but complementary angles. First, it explores what can be gained by reading Lycophron's poem against the backdrop of Callimachus' poetry. It contends that the Alexandra presents a radical and polemical departure from the Alexandrian's poetic programme, pointedly appropriating key Callimachean images while also countering Callimachus' apparent dismissal of the 'noisy' tragic genre. Previous scholarship has noted links between the openings of the Aetia and of the Alexandra, but this article demonstrates that this relationship is only one part of a larger aesthetic divide between the two poets: by embracing the raucous acoustics of tragedy, Lycophron's poem offers a self-conscious and agonistic departure from Callimachus' aesthetic preferences. Second, this article considers another way of conceiving the aesthetics of the poem beyond a Callimachean frame, highlighting how Lycophron pointedly engages with and evokes earlier Aristotelian literary criticism concerning the 'frigid' style: the Alexandra constructs its own independent literary history centred around the alleged name of its author, 'Lycophron'. The article proposes that this traditional attribution is best understood as a pen name that signposts the poem's stylistic affiliations, aligning it not so much with the Ptolemaic playwright Lycophron of Chalcis but rather with Lycophron the sophist and a larger rhetorical tradition of stylistic frigidity. Ultimately, through these two approaches, the article highlights further aspects of the Alexandra 's aesthetic diversity.